Ultrasound and Carcass Merit of Youth Market Cattle - Chad Carr; Dwain Johnson; Mark Shuffitt (EDIS)
Market cattle shown at county and state fairs and other youth shows across the United States are food animals. The endpoint value of food animals is primarily based on their carcass merit. Ideally, carcass merit should be assessed from actual carcasses. However, when carcass data cannot be collected, ultrasound evaluation of market cattle is an excellent method to accurately assess differences in fat thickness, ribeye area, and percentage of intramuscular fat within the ribeye. This 7-page fact sheet was written by Chad Carr, Dwain Johnson, and Mark Shuffitt, and published by the UF Department of Animal Science, June 2012.